Morphological Variation of Anterior Clinoid Process in Dry Human Skulls - Dhakal, Arun; Mehta, Umesh Kumar; Sah, Sanjib Kumar; Kumar Chaudhary, Raju Kumar Chaudhary (Birat Journal of Health Sciences, 2020)
Introduction: The anatomical relationship of the Anterior Clinoid Process (ACP) with its neighboring structures in the base of the skull is complex with different variations. Thus, study of its morphology is essential in defining and directing surgery. Objective: This study aims to investigate the anatomy of the anterior clinoid process and prevalence of Caroticoclinoid foramen (CCF) to highlight its variations. Methodology: The measurements were performed in 31 dry human skulls to define the structure of ACP, the presence of CCF and other relevant landmarks using digital Vernier Calipers. Results: The mean length, basal width and thickness of the right ACP was 9.88+/- 1.36 mm, 8.72+/-1.50 mm, and 5.21+/-1.83 mm respectively and that of the left was 10.30+/-1.47, 8.73+/-1.71, and 5.33+/-1.60 mm respectively. Paired t-test was used to compare the mean of these sides. Type III was the most common form of ACP for both the sides. Out of 31 skulls, CCF was observed in 12 (38.7%) skulls with 7 (22.6%) in right and 5 (16.13%) in left side. Distances between neighboring ACP’s, between Posterior Clinoid process (PCP), between ACP to Crista Galli (CG) and ACP to PCP were 24.41+/-2.32, 20.01+/-3.23, 31.6+/-2.20, and 8.30+/-3.10 mm respectively. Conclusion: This article highlights the detailed morphology of ACP. There is variation in relation to its dimensions across other studies. This study also explores the prevalence of CCF and parasellar landmarks in relation to ACP giving an idea of the exposure achievable during surgical approach of the region.